2008
DOI: 10.3814/2008/814849
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of YKL-39 Gene in Glial Brain Tumors

Abstract: More than forty genes with considerably increased expression in glioblastoma as compared to normal human brain were identified by SAGE. One of the most prominent among them was CHI3L2 (YKL-39) gene, which encodes 39 kDa chitinase-like protein.Northern blot hybridization confirmed the data of SAGE for the majority of glioblastomas. Anaplastic astrocytomas could be divided on two groups: in one of them the YKL-39 expression was completely undetectable, but in the other group quite high contents of YKL-39 mRNA we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 22 publications
0
15
0
3
Order By: Relevance
“…Previously using Serial Analysis of Gene Expression (SAGE), Northern blotting and PCR analysis we have shown the increasing YKL 39 gene expression in glioblastomas. However, Western blot analysis did not show simultaneous production of YKL 39 and YKL 40 [19] in spite of high degree of their sequence identity.…”
Section: Chitinase 3 Like Protein 2 (Chi3l2 Ykl 39) Activates Phosphmentioning
confidence: 85%
See 2 more Smart Citations
“…Previously using Serial Analysis of Gene Expression (SAGE), Northern blotting and PCR analysis we have shown the increasing YKL 39 gene expression in glioblastomas. However, Western blot analysis did not show simultaneous production of YKL 39 and YKL 40 [19] in spite of high degree of their sequence identity.…”
Section: Chitinase 3 Like Protein 2 (Chi3l2 Ykl 39) Activates Phosphmentioning
confidence: 85%
“…After restriction of pGemT Easy CHI3L2 [19], the Nde I/Xho I fragment was subcloned in expression vector pET 24a (+) from «Novagen» (Germany). The nucleotide sequence was checked by the dideoxy method («3130 Genetic Analyzer, Applied Biosystems», USA).…”
Section: Chitinase 3 Like Protein 2 (Chi3l2 Ykl 39) Activates Phosphmentioning
confidence: 99%
See 1 more Smart Citation
“…YKL-39 is secreted from articular chondrocytes (13). YKL-39 mRNA has been detected in lung, heart, and glioblastoma but not in brain, spleen, or pancreas (13,16). YKL-39 mRNA was also detected in macrophages that were strongly stimulated by a combination of IL-4 and TGF-␤ (17).…”
mentioning
confidence: 99%
“…Our recent studies revealed that both CHI3L1 and CHI3L2 genes are upregulated in glioblastoma [22,23]. However, their expression levels differ and often are not simultaneous, at the level of both mRNA and protein.…”
Section: T T T T T T T T T Chi3l1mentioning
confidence: 99%